Recent Advancements in Targeted Delivery of Therapeutic Molecules in Neurodegenerative Disease - Spinocerebellar Ataxia - Opportunities and Challenges - Satya Prakash; Meenakshi Malhotra (AboutScience Srl, 2008)
Drug discovery and its methodologies have been very effective in terms of treating cancers and immunological disorders but have not been able to stop genetic diseases as most of the drugs target at the protein level. They merely mitigate the symptoms of the disease. Spinocerebellar ataxia is a neurological genetic disorder that is caused by the formation of an abnormal protein. There have been several reports on ataxic drug development but actual clinical treatment is yet to be achieved. Oligonucleotide therapy called sequence specific siRNA mediated gene silencing has evolved with promising results. This approach emphasizes on suppressing the expression of the diseased gene at mRNA level. However, there is a limitation in delivery of siRNA to the target site. Several methods have been developed over the last decade to enhance the target specific delivery of DNA, siRNA, protein and small drug molecules for therapeutic purpose with less or no side effects. This review discusses the latest upcoming technologies in the field that focus on a number of nonviral nanocarriers for targeted delivery. In this review, we explore the promise and potential of novel therapeutics with interest on ataxia therapy.